Effects of Various Bioactivator Applications on Sapling Development of Passionflower and Guava Plantles - Canan Nilay Duran; Gizem Demirkaplan; Sevinç Şener (Turkish Journal of Agriculture: Food Science and Technology)
Passionflower is a member of Passifloraceae family, it can be used as medicinal and ornamental plants in addition to its consumption as fruit in the world. Guava (Psidium guajava L.) fruits, which has a rich nutrient content, are consumed both fresh and processed. Passionfruit and guava plants, which can only be cultivated in temperate southern coasts in our country, have gained commercial importance because of the fruits' export potential, high medical importance and nutrient. This study was carried out to determine the effects of some bioactivator applications on the criteria of sapling growth and development of passionflower and guava plants. The experiment was conducted between 2018-2019 under greenhouse conditions. Saplings obtained from seed germination in Akdeniz University Faculty of Agriculture Research and Experiment Area were used as plant material. 3 different commercial preparations called Messenger, Crop-set and ISR-2000 were used as bioactivators. Plant height (cm), stem diameter (mm) and number of leaves (number / plant) were measured weekly, in order to determine the effect of the applications on the growth and development of saplings. At the end of the study, it was determined that the highest average plant height (10.17 cm), stem diameter (13.53 mm) were obtained in ISR-2000 application. The highest average plant height (11.93 cm), stem diameter (16.44 mm) and number of leaves (9.07 units / plant) were obtained from Messenger application in guava plant. When the results obtained are evaluated, it is recommended that ISR-2000 bioactivator can be applied in passionflower sapling cultivation and Messenger bioactivator can be applied for guava sapling cultivation.